Pembiasaan Kegiatan Keberagamaan dalam Membentuk Karakter Siswa SDIT Nur El-Qolam Serang Banten - Nurdiyanto, Nurdiyanto; Tarsono, Tarsono; Hasbiyallah, Hasbiyallah (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
In fact, the habit of religious activities has proven to be influential in forming students' character. Judging from the attitudes and behavior of students who are accustomed to carrying out religious activities and those who are not accustomed to participating in religious activities. This research aims to describe and analyze the religious activity habits of students at SDIT Nur El-Qolam Serang Banten. This research uses a qualitative approach with field study methods (library research). Meanwhile, the data sources used in this research contain two primary and secondary sources. The primary includes interviews with several first-grade students taken from one class and a parallel first-grade teacher as a secondary source of reinforcement. Meanwhile, secondary data includes intermediary media such as journals, proceedings, and documents on students' religious activities monitored by their respective class teachers. Apart from that, the data collection techniques used in this research include observation, interviews, and taking notes. Meanwhile, the data analysis techniques used use the Miles and Huberman theoretical model, including data reduction, data presentation, and data verification or conclusions. The results of this research show that the concept of character education contains several findings including (1) first-grade students routinely use it; (2) religious programs; (3) formation of student character; and (4) inhibiting and supporting factors in implementing religious program activities.